Heterogeneous catalytic reduction of substituted 5-acyl-1,3-dioxanes - A. I. Musin; Yu. G. Borisova; G. Z. Raskil’dina; R. R. Daminev; A. R. Davletshin; S. S. Zlotskii (Тонкие химические технологии, 2022)
Objectives. To study the hydrogenation of substituted 5-acyl-1,3-dioxanes in the presence of metal-containing catalysts (Pt/Re, Pd/C, Ni/kieselguhr, and Ni/Mo).Methods. In order to determine the qualitative and quantitative composition of the reaction masses, the following analysis methods were used: gas-liquid chromatography (using the Kristall 2000 hardware complex); mass-spectroscopy (using Chromatec-Kristall 5000M device with NIST 2012); nuclear magnetic resonance (NMR) spectrometry (using Bruker AM-500 device with operating frequencies of 500 and 125 MHz).Results. Hydrogenation of substituted 5-acyl-1,3-dioxanes obtained by condensation of carbonyl compounds with paraformaldehyde and sulfuric acid was used to synthesize heterocyclic alcohols in the presence of metal-containing catalysts with a conversion of the initial ketones of 60–90% and a formation selectivity of target products of 70–90%. Substances were analyzed and confirmed by gas-liquid chromatography, mass spectrometry and NMR spectroscopy.Conclusions. The best catalyst for the reduction of substituted 5-acyl-1,3-dioxanes is Pd/C. By using this catalyst, it is possible to achieve a high selectivity for the formation of the corresponding heterocyclic alcohols at a conversion rate of the initial ketones of 60–90%.